PEDAGOGICAL INNOVATIONS IN PROFESSIONAL EDUCATION AND THEIR CONTENT - Pirmatov Barkamoljon Gayratjonovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the role and importance of innovations in the development of society, the meaning and essence of the concept of innovation, and the specific features of using pedagogical innovations in the professional education system. Also, the history of the emergence of innovations is briefly covered. Pedagogical aspects of innovations and their role in the process of professional education are analyzed. Innovation is considered as a system and the main features of innovation are distinguished. The laws of innovation have been studied.